Social Representations of Trans People in the Workplace - José Baptista; Dália Costa; Sónia P. Gonçalves (Social Sciences, 2023)
Organizations show tendencies to discriminate against trans people, making them significantly more likely to face barriers in the professional context, where the highest rates of discrimination against trans people are reported. This study intends to acknowledge the SRs that are associated with trans people in the workplace since the Theory of Social Representations suggests that Social Representations (SRs) are useful to regulate perceptions and the way we act in the world. Also, through Intergroup Contact Theory, by suggesting that contact with a minority population will reduce the associated prejudice, we also intend to understand the impact contact has on SRs. By applying a questionnaire between 20 January and 21 February 2022 on a random sample of 217 people, and respective analyses in MAXQDA 2022 and EVOC 2005 software, the results indicate that the SRs most associated with trans people in a professional context are discrimination, normality, equality, difficulties, and prejudice. Although the term “discrimination” was the most mentioned, it is worth underlining the appearance of positive (and neutral) terms, which may, according to Intergroup Contact Theory, be justified by contact since the majority of the sample (57.6%, n = 125) have had contact with trans people.